PERTIMBANGAN HAKIM DALAM MENENTUKAN KADAR NAFKAH MADHIYAH, NAFKAH IDDAH DAN MUT’AH TERHADAP PERKARA CERAI TALAK - Nurul Rifdah Herman; Musyfikah Ilyas; Nurfaika Ishak (Universitas Islam Negeri Alauddin Makassar, 2023)
This study discusses the considerations of judges in determining the leves of madhiyahinco, Iddah dan mut’ahmaintenance of divorce cases (a case study at the Sungguminasa religions court class 1B). Household disharmony resulting from the neglect of rights and obligations which causes the breakup of the marriage. One of the consequences in the from of burdening the husband to pay for madhiyah maintenance, iddah dan mut’ah living. This research aims to find out what is the legal basic for providing maintenance and what are the inhibiting factors in providing levels of madhiyah maintenance, iddah income and mut’ah against disvorce. As for the result of this study, in giving consideration to determining the level of living, the panel of judges is based on the first two things based on the husband’s income (economic factors) and the wife basic needs. Another consideration is that there are no factors that become ostacles in providing madhiyah maintenance, iddah and mut’ah maintenance specifically at the Sungguminasa religious court. However, in general, the compilation of Islamic law, article 80, paragraph 7, has been absorbed as an obstacle to earning a living, namely nusyuz. The implication is tp provide advice to layers of society related to the protection of women’s rifht after good, if and a husband is required to provide maintenance for his wife in a godd way, if it is not implemented the it is considered debt. Keyword: Judge’s consderation, Madhiyah income, Iddah Income, Mut’ah and divorce.